2013
DOI: 10.1016/s1734-1140(13)71055-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of multiple Transient Receptor Potential channel genes in murine 3T3-L1 cell lines and adipose tissue

Abstract: Abstract:Background: Calcium and its signaling have a role in adipogenesis. Transient Receptor Potential (TRP) channels are non-selective cation channels with a high permeability to calcium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 14 publications
5
55
2
2
Order By: Relevance
“…Thus, it is likely that different heat sensitive channels (warm temperature 25~40C and heat temperature >40°C) exist in 3T3-L1 pre-adipocytes. The RT-PCR and immunoblot analyses revealed that TRPV1, TRPV2, and TRPV4 mRNA and protein are definitely expressed in mouse 3T3-L1 pre-adipocytes and differentiated adipocytes, which is compatible with the previous paper [46]. From these observations, it is likely that adipose cell possess multiple functional thermo-sensitive TRPVs, where TRPV4 and TRPV1/TRPV2 are involved.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, it is likely that different heat sensitive channels (warm temperature 25~40C and heat temperature >40°C) exist in 3T3-L1 pre-adipocytes. The RT-PCR and immunoblot analyses revealed that TRPV1, TRPV2, and TRPV4 mRNA and protein are definitely expressed in mouse 3T3-L1 pre-adipocytes and differentiated adipocytes, which is compatible with the previous paper [46]. From these observations, it is likely that adipose cell possess multiple functional thermo-sensitive TRPVs, where TRPV4 and TRPV1/TRPV2 are involved.…”
Section: Discussionsupporting
confidence: 90%
“…93) TRPV2 has been reported expressed in WAT and BAT. 56) We previously showed that TRPV2 is more highly expressed in mouse brown adipocytes than TRPV1, TRPV3, TRPV4, and TRPM8. 57,94) Our results demonstrated that primary TRPV2-deficient (TRPV2KO) adipocytes show decreased mRNA levels of multiple genes involved in mitochondrial oxidative metabolism, such as Ucp1 and PPARγ coactivator 1-alpha (Ppargc1α).…”
Section: Trpv2mentioning
confidence: 95%
“…13) TRPV1 is expressed in brown adipocytes, [55][56][57] and adipocyte cell lines such as the HB2 brown adipocyte cell line and the 3T3-L1 adipocyte cell line. 55) In 3T3-L1 cells, activation of TRPV1 by capsaicin induces calcium influx and prevents adipogenesis.…”
Section: Role Of Thermo-sensitive Trp Channels In Adipose Tissuementioning
confidence: 99%
“…The high-fat diet was the same as above, and rutin was added into the food following the recipe strictly by the researchers; 4. HFD combined with treadmill running group (HE) group: the mice were allowed a HFD ad libitum as above (2) and also underwent treadmill training at a intensity of 15 m/min, 60 min per day, and five times/ week during the whole period of experimentation (i.e., 16 weeks); 5. HFD combined with treadmill running and rutin intervention group (HRE) group: the mice were allowed a HFD ad libitum supplemented with 0.1 % rutin as above (3) and also underwent treadmill training as above (4) during the whole period of experimentation (i.e., 16 weeks).…”
Section: Treatment Of Animalsmentioning
confidence: 99%
“…Transient receptor potential cation channel subfamily V member 4 (TRPV4) is a calcium-permeable nonselective ion channel membrane that is highly expressed in white AT [2], and recent evidence suggests that TRPV4 might be a new critical player for regulating adipose tissue function [29]. Specifically, work from Spiegelman's group revealed that TRPV4 acts as a cell-autonomous mediator for both the thermogenic and pro-inflammatory programs in adipocytes [29].…”
Section: Introductionmentioning
confidence: 99%